2023
DOI: 10.1101/2023.04.13.536723
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disturbance increases functional diversity but decreases phylogenetic diversity of an arboreal tropical ant community

Abstract: Tropical rainforest canopies host a highly diverse arthropod fauna, which contribute to ecosystem function through their functional (FD) and phylogenetic diversity (PD). While a lot of previous research has documented the severe negative impacts of disturbance on the FD and PD of ground invertebrate communities, our understanding of arboreal counterparts is limited. Here, we studied the effects of forest disturbance on an ecologically important invertebrate group, the ants, in a lowland rainforest in New Guine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 84 publications
(109 reference statements)
1
1
0
Order By: Relevance
“…Regarding phylogenetic diversity, we observed that −NTI was considerably higher in the oak forest than in the induced grassland. This result agrees with our initial hypothesis and other studies documenting decreased phylogenetic diversity in areas affected by environmental disturbance (Liu et al 2016, Arnan et al 2018, Hoenle et al 2023. In many of these studies, a greater phylogenetic diversity comes from the positive relationship between the number of species in the local assemblage and evolutionary divergence, i.e.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding phylogenetic diversity, we observed that −NTI was considerably higher in the oak forest than in the induced grassland. This result agrees with our initial hypothesis and other studies documenting decreased phylogenetic diversity in areas affected by environmental disturbance (Liu et al 2016, Arnan et al 2018, Hoenle et al 2023. In many of these studies, a greater phylogenetic diversity comes from the positive relationship between the number of species in the local assemblage and evolutionary divergence, i.e.…”
Section: Discussionsupporting
confidence: 93%
“…All data and R scripts underlying this work are publicly available in the Zenodo Digital Repository: https://doi.org/10.5281/zenodo.10624632 (Hoenle et al., 2024).…”
Section: Data Availability Statementmentioning
confidence: 99%